1981
DOI: 10.1016/0304-3959(81)90134-2
|View full text |Cite
|
Sign up to set email alerts
|

Age-associated changes of responses to acetylsalicylic acid

Abstract: Aspirin can be an effective antipyretic, analgesic and anti-inflammatory agent, but unfortunately, its use in the elderly is often excessive [43]. In a survey by Gillies and Skyring, the overall prevalence of daily aspirin intake was greater in middle-age and older-age groups than for those of less than 40 years of age [16]. The elderly are susceptible to the advertising of non-prescription drugs and aspirin is frequently self-prescribed [8,31]. Age-related physiological changes modify the response to aspirin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
1994
1994

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Others (Armstrong & Blower, 1987;Walt et al, 1986) have also reported a rising prevalence of NSAID usage with age which may reflect a higher incidence of musculoskeletal disorders and pain reporting (Baskin et al, 1981). More females reported using NSAIDs than males for each age division studied.…”
Section: Discussionmentioning
confidence: 99%
“…Others (Armstrong & Blower, 1987;Walt et al, 1986) have also reported a rising prevalence of NSAID usage with age which may reflect a higher incidence of musculoskeletal disorders and pain reporting (Baskin et al, 1981). More females reported using NSAIDs than males for each age division studied.…”
Section: Discussionmentioning
confidence: 99%